Journal publishing in the era of economic crisis: a case of scientific journals in the field of social sciences in Croatia - Vrana, Radovan (Array, 2011)
The purpose of this article is to present findings from the research of aspects of journal publishing in the field of social sciences in Croatia in changing working conditions caused by the rapid development of information and communication technology. This paper is based on an online survey of 79 journals in the field of social sciences in Croatia. Findings indicate a dual publishing nature of the scientific journals as they exist both in the traditional paper based and in the electronic environment. In addition to slow shift towards publishing exclusively in the electronic environment, editorial teams cope with insufficient financial support for the publication of printed versions of their journals, low-quality of article submissions, badly formatted articles, lack of help to the editor, etc. Researched journals use the internet for the improvement of the interaction with authors, reviewers and readers and digital repositories for long-term storage of articles. To remain relevant to the scientists in Croatia, researched journals must be led by professional editorial teams whose only job will be management of the journal they work for. Originality/value – The paper contributes to the growing body of knowledge about current developments in scientific journal publishing under the influence of information and communication technology.